A mutation in the serine protease TMPRSS4 in a novel pediatric neurodegenerative disorder - Lahiry, Piya; Racacho, Lemuel; Wang, Jian; Robinson, John F; Gloor, Gregory B; Rupar, C A; Siu, Victoria M; Bulman, Dennis E; Hegele, Robert A (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background To elucidate the genetic basis of a novel neurodegenerative disorder in an Old Order Amish pedigree by combining homozygosity mapping with exome sequencing. Methods and results We identified four individuals with an autosomal recessive condition affecting the central nervous system (CNS). Neuroimaging studies identified progressive global CNS tissue loss presenting early in life, associated with microcephaly, seizures, and psychomotor retardation; based on this, we named the condition Autosomal Recessive Cerebral Atrophy (ARCA). Using two unbiased genetic approaches, homozygosity mapping and exome sequencing, we narrowed the candidate region to chromosome 11q and identified the c.995C > T (p.Thr332Met) mutation in the TMPRSS4 gene. Sanger sequencing of additional relatives confirmed that the c.995C > T genotype segregates with the ARCA phenotype. Residue Thr332 is conserved across species and among various ethnic groups. The mutation is predicted to be deleterious, most likely due to a protein structure alteration as demonstrated with protein modelling. Conclusions This novel disease is the first to demonstrate a neurological role for a transmembrane serine proteases family member. This study demonstrates a proof-of-concept whereby combining exome sequencing with homozygosity mapping can find the genetic cause of a rare disease and acquire better understanding of a poorly described protein in human development.